The effectiveness of abdominal stretching exercise versus breathing relaxation with nature sounds on the level of dysmenorrhea - Faridah Umamah; R. Khairiyatul Afiyah (Healthcare in Low-resource Settings)
Menstruation usually comes accompanied by several complaints, such as dysmenorrhea. The intervention of abdominal stretching and breathing relaxation with Nature sounds can increase muscle relaxation so as to reduce menstrual pain. This study aimed to analyze the effectiveness of abdominal stretching exercise versus breathing relaxation with nature sounds on dysmenorrhea levels. This study was a quasi-experimental design with a two-group comparison using a pre-test and post-test approach. The experimental group received abdominal stretching, while the control group underwent breathing relaxation with nature sounds. The inclusion criteria were adolescents aged 11–20 years who experienced primary dysmenorrhea. The total sample consisted of 30 young women in the abdominal stretching intervention group and 30 young women in the breathing relaxation with nature sounds group. Data were collected using a pain assessment instrument, namely the Numerical Rating Scale (NRS). The data were analyzed using paired t-tests to measure differences in pre-test and post-test scores within the groups and independent sample t-tests to compare post-test scores between the two groups. The results of the paired T-test showed that abdominal stretching and breathing relaxation with nature had an effect on pain level during menstruation with p-value was 0.000 (p < 0.05). After the intervention, the menstrual pain was reduced in both groups. Abdominal stretching exercise and breathing relaxation with Nature sounds were able to reduce menstrual pain in adolescent girls, therefore these interventions were recommended for young women who experience primary dysmenorrhea.